2014
DOI: 10.4049/jimmunol.1401750
|View full text |Cite
|
Sign up to set email alerts
|

The C5a Anaphylatoxin Receptor (C5aR1) Protects against Listeria monocytogenes Infection by Inhibiting Type 1 IFN Expression

Abstract: Listeria monocytogenes is a major cause of mortality resulting from food poisoning in the United States. In mice, the fifth complement component (C5) has been genetically linked to host resistance to listeriosis. Despite this genetic association, it remains poorly understood how C5 and its activation products, C5a and C5b, confer host protection to this Gram-positive intracellular bacterium. Here we show in a systemic infection model that the major receptor for C5a, C5aR1, is required for a normal robust host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Thus, deficiency of C5a was most likely responsible for the increased susceptibility of A/J mice. Our work in C5aR1 deficient mice now supports this hypothesis (Calame et al, 2014). C5aR1−/− mice were highly susceptible to L. monocytogenes infection, with higher bacterial burdens and reduced survival in comparison to WT mice.…”
Section: Role Of the C3a And C5a Receptors In Listeriosissupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, deficiency of C5a was most likely responsible for the increased susceptibility of A/J mice. Our work in C5aR1 deficient mice now supports this hypothesis (Calame et al, 2014). C5aR1−/− mice were highly susceptible to L. monocytogenes infection, with higher bacterial burdens and reduced survival in comparison to WT mice.…”
Section: Role Of the C3a And C5a Receptors In Listeriosissupporting
confidence: 79%
“…Similarly, TRAIL, a downstream target of type 1 IFN and a major driver of L. monocytogenes -induced splenocyte apoptosis, was significantly upregulated in splenic NK cells in C5aR1−/− mice. Finally, blockade of the type 1 IFN receptor rescued C5aR1−/− mice from L. monocytogenes -induced mortality (Calame et al, 2014). Subsequent work from our lab has clarified the mechanism by which C3a and C5a regulate type 1 IFN expression.…”
Section: Role Of the C3a And C5a Receptors In Listeriosismentioning
confidence: 99%
“…Notably, previous measurements of IFNα concentrations in either serum or spleen ranged from 30–50 pg/mL of 24 hours after i.v. Lm infection (47, 48). This may indicate that IFNα is produced by cell types that we did not include in high numbers in our splenocyte cultures.…”
Section: Discussionmentioning
confidence: 99%
“…C3aR and C5aR1 are expressed on both myeloid and lymphoid cells, as well as on multiple types of non-immune tissue cells (5). In our previous studies, we showed that C3aR (6) and C5aR1 (7) are protective during systemic Lm infection. Compared to WT mice, C3aR−/− mice and C5aR1−/− mice had decreased survival, increased bacterial burdens in the liver and spleen, increased cytokine production, including IFN-β, increased spleen and liver pathology, and increased apoptosis in the spleen.…”
Section: Introductionmentioning
confidence: 91%
“…Compared to WT mice, C3aR−/− mice and C5aR1−/− mice had decreased survival, increased bacterial burdens in the liver and spleen, increased cytokine production, including IFN-β, increased spleen and liver pathology, and increased apoptosis in the spleen. Pre-treatment of the C5aR1−/− mice with an antibody to the type I interferon receptor-1 (IFNAR-1) protected these mice from Lm -induced mortality (7), indicating that excess IFN-β production in the C5aR1−/− mice leads to increased susceptibility to Lm . Production of type I interferons during Lm infection is detrimental to the host (810).…”
Section: Introductionmentioning
confidence: 99%